Subharmonic solutions and minimal periodic solutions of first-order variant subquadratic Hamiltonian systems - Tang, Shanshan; Zhang, Xiaofei (Topological Methods in Nonlinear Analysis, 2020)
Using the homological link theorem and iteration inequalities of Maslov-type index, we prove the multiplicity of subharmonic solutions for some variant subquadratic non-autonomous Hamiltonian systems. Moreover, the minimal period problem has also been considered for the variant subquadratic autonomous Hamiltonian systems.